Conflict competence of students of the educational environment of a higher educational establishment: a study of the formation dynamics - I. V. Belasheva; M. I. Plugina; M. L. Esayan (Кардиоваскулярная терапия и профилактика)
Aim. To present the system-level structure of conflict competence and study the interrelations and differences in its components in students in the context of studying at a university.Material and methods. The study involved 150 1-4-year students. According to the factor analysis of psychological variables, 5 empirically represented groups of parameters were identified, con sidered as conflict competence. The empirical study used psychodiagnostic techniques aimed at determining strategies of behavior in conflict situations; personal aggressiveness and conflict; style of self-regulation of behavior; communicative tolerance; level of development of reflexivity and the technique of coping mechanisms.Results. According to Kruskal-Wallis H test, there were differences in 3 competencies: sthenic intrapersonal-oriented conflict readiness; interpersonal-oriented conflict competence; intrapersonal con-flictogenity. There were no significant differences in emotive-personal conflict readiness and constructive-activity conflict competence.An analysis of the prevalence of high level of conflict competence formation showed that in 1st-year students, emotive-personal conflict readiness prevails, in the 2nd year — constructive-activity competence, in 3rd year — intrapersonal conflictogenity, in 4th — interpersonal-oriented competence. Thus, the period of study at a university can be considered as a stage in the formation of conflict competences.Conclusion. The data obtained make it possible to identify five conflict competences, reflecting the motivational, cognitive and behavioral components of conflict tolerance and conflict readiness, which ensure the perception and analysis of conflict situations, the organization of behavior and communication in conflict situations and the willingness to solve them; the resulting five-factor statistical conflict competence model details the proposed two-factor theoretical model and refines it in terms of mechanisms. A comparative analysis of representation of conflict competences among 1-4-year students determined the competence dynamics as follows: from conflict instability to conflict readiness, which allows to clarify the existing ideas about the stages and features of competence formation under the influence of educational activities at the university.